(untitled) (American Journal of Business Management, Economics and Banking, 2026)
At the present time, one of the most pressing scientific problems in the practice of auditing is to eliminate a number of problems that need to be solved in the process of reviewing, conducting and generalizing the results of audits, improving their theoretical and methodological foundations. These are, firstly, the inability to apply the rules and regulations on accounting and auditing activities to the level of requirements in audit practice, secondly, the insufficient study of the methodological aspects of the organization and conduct of the audit, thirdly, the inability to generalize and formalize the results of the audit in the audit work in accordance with the current requirements, and secondly, the risk of auditing, the lack of transparency On the other hand, such situations as the definition of indicators of the quality of audit work and the effectiveness of audit organizations and the method of its assessment are not developed at the level of modern requirements..